Impact of Discovery Learning Model on Students' Critical Thinking Skills in Mathematics Learning - Safitri, Avida Nurisa; Fathonah, Nur; Faizah, Hanim; Prayitno, Lydia Lia (Journal of Education and Learning Mathematics Research (JELMaR), 2025)
Critical thinking abilities and mathematical content are closely related since students must use critical reasoning, analysis, and problem-solving techniques to grasp mathematical ideas. However, field data reveals that many students still experience difficulties in developing adequate mathematical critical thinking abilities. This study aims to investigate the influence of implementing the Discovery Learning model on students’ mathematical critical thinking skills. The research employed a quantitative approach with a quasi-experimental design. The population included all grade X students at SMAN 1 Driyorejo in the academic year 2024/2025. Through purposive sampling, two classes were selected as research samples: class X-1 as the control group taught using conventional learning methods such as lectures and repetitive practice, and class X-5 as the experimental group that received instruction through the Discovery Learning model. Data were collected through a posttest administered after the learning intervention. The instrument consisted of five story-based questions centered on arithmetic sequences, designed to assess students’ critical thinking in mathematics. The data analysis process began with the normality test using the Chi-Square method, followed by a homogeneity test using the F-test to validate statistical assumptions. Upon meeting these requirements, the t-test was conducted to examine the research hypothesis and compare the posttest results of both groups. The findings revealed that the Discovery Learning model had a significant positive impact on students’ mathematical critical thinking skills. Therefore, it is recommended that this model be utilized more broadly across various subject matters and educational levels to foster deeper engagement and critical thinking among students.